2020
DOI: 10.1371/journal.pone.0231816
|View full text |Cite
|
Sign up to set email alerts
|

Association of early viral lower respiratory infections and subsequent development of atopy, a systematic review and meta-analysis of cohort studies

Abstract: OPEN ACCESSCitation: Kenmoe S, Kengne-Nde C, Modiyinji AF, Bigna JJ, Njouom R (2020) Association of early viral lower respiratory infections and subsequent development of atopy, a systematic review and meta-analysis of cohort studies. PLoS ONE 15(4): e0231816. https://doi.org/10.inhaled allergens (OR = 4.2, [95% CI = 2.1-8.5]), or furred animals (OR = 0.6, [95% CI = 0.5-0.9]). ConclusionThese results suggest that there is no association between viral LRTI at < 5 years and the majority of categories of atopy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
1
3
0
3
Order By: Relevance
“…Some studies found an increased risk of allergic sensitization 41 , other reported protection against allergic sensitization through the stimulation of Th-1 cytokine production 42 , whereas others did not find any influence of childhood viral LRTI on the risk of subsequent atopy 11 . The results of a recent systematic review and meta-analysis suggest, as ours, that there is no association between viral LRTI at < 5 years and positivity of skin prick test or atopic dermatitis, but, in contrast, there is a higher frequency of allergic rhinoconjunctivitis (OR = 1.7 [95%CI = 1.1–2.9]) 43 .…”
Section: Discussionsupporting
confidence: 55%
“…Some studies found an increased risk of allergic sensitization 41 , other reported protection against allergic sensitization through the stimulation of Th-1 cytokine production 42 , whereas others did not find any influence of childhood viral LRTI on the risk of subsequent atopy 11 . The results of a recent systematic review and meta-analysis suggest, as ours, that there is no association between viral LRTI at < 5 years and positivity of skin prick test or atopic dermatitis, but, in contrast, there is a higher frequency of allergic rhinoconjunctivitis (OR = 1.7 [95%CI = 1.1–2.9]) 43 .…”
Section: Discussionsupporting
confidence: 55%
“…Sensitivity analyses that included only studies with a low risk of bias and studies comparable with regard to confounding factors were performed to enhance the accuracy of our results. We determined the comparability of studies with confounding factors using Chi-square, Fisher or Student's T-test as reported previously [32].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo americano, mostrou associação significativa com o uso de antibióticos (OR 1.42); H2RA (OR 1.48) e IBP (OR 1.15) e o desenvolvimento de alergia ocular 30 . O uso de antibiótico e paracetamol no primeiro ano de vida, também se apresentou como fator de risco para conjuntivite alérgica na criança (6-7 anos) e adolescente (13-14 anos) 19,35 , porém a infecção de trato respiratório inferior não teve associação 22 .…”
Section: Discussionunclassified